The Prevalence of Exposure to Violence Among Healthcare Professionals in Adana and Their Opinion on Violence in Health - Yılmaz, Kemal; Kaya, Kenan; Özesen, Toygün Anıl; Hilal, Ahmet (The Bulletin of Legal Medicine, 2023)
Objective: Workplace violence is an important source of problem for employees worldwide. The present study aimed to identify the prevalence of exposure to violence among healthcare professionals, the type of violence they experienced and influencing occupational features, and to determine the healthcare professionals’ opinion about the causes of violence and the potential measures to be taken against violence in health.Methods: A 37-question survey was performed in 598 medical doctors and 357 healthcare assistants including nurses as well in Adana, Türkiye. Results: Of the 955 healthcare professionals participated in the study, 48.5% were male and 51.5% were female, and 85.9% have been subjected to violence at least once in their professional lifetime. The most common type of violence was psychological or verbal attack, which stated to be most frequently committed by the patient relatives and by male gender. Male healthcare workers were exposed to statistically significantly more physical violence. There was statistically significant correlation between the number of patients healthcare professionals dealt with in a day and the rate of exposure to violence. It was found that those who had been exposed to physical violence filed a complaint more than those who had been subjected to other forms of violence. Conclusion: High rates of violent behaviour against healthcare workers are at worrying levels indicating that violence in health is a critical problem. Solution of this problem requires all parties’, primarily the health policy makers’ undertaking important tasks.
Keywords: Violence; Healthcare professionals; Physician; Physical Violence; Psychological violence